Analisis Resepsi Khalayak mengenai Hipnotis dalam Program â€œGaris Tangan (Episode 195)â€ ANTV - Santi Delliana; Ayu Wiranti (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2023)
People see in reporting that hypnotic is usually used as a fraud mode, increasing people's concerns about hypnotics. Various impressions in the media also show that hypnotics are now used as a hypnotherapy method, but hypnotics are used in the media as an entertainment concept. The Garis Tangan program is an entertainment program that brings the theme of a new concept about hypnosis. From the program, the purpose of this research is to find out how the Bandung Hypnotic Community interprets hypnotics in a reality show program, "Garis Tangan (Episode 195)" on ANTV. The method used is Audience Reception Analysis, which has three categories: Stuart Hall, Dominant Hegemony, Negotiation, and Opposition. The theory in this research is encoding-decoding. The paradigm used by Constructivism researchers is a qualitative approach. The results of this study are that the three informants of the Bandung Hypnotic Community are included in the Negotiation category, and one informant is included in the Opposition category. This shows that the informant is an active audience by issuing different responses to understand the message given by the media.